Intersecting discourses : the interaction of the libertine and the sentimental discourse in mid-eighteenth century French and English novels - Fourny, Corinne (2004)
French and English literature in the eighteenth century are generally held to have a symbiotic relationship and the links between the two sentimental traditions, in particular, have been well documented by scholars. However the connections between the sentimental and the libertine discourse have tended to be obliterated. The main assumption underlying this project is the existence of an intimate interplay between sentimentalism and libertinism. Its main aim is to trace the strong attraction existing between the two and to question the genre and national dimensions which have been perpetuated by previous critical discourses through close textual analyses of mid-century French and English novels (Sterne's A Sentimental Journey and Crebillon's Les Egarements du Coeur et de I 'esprit and Les Heureux Orphelins, Haywood's The Fortunate Foundlings, Riccoboni's Lettres de Milady Juliette Catesby, Burney's Evelina, and Cleland's Fanny Hill). The focus will be on the moment when the libertine is tempted to behave sentimentally or when the sentimental (wo)man is tempted to act as a libertine. The relationships between these core texts being very rich, they will be approached from different perspectives in each of the issue-based chapters which will centre on questions of language, non-linguistic communication, sociability, epistolarity and difference.